POTENTIAL OF ANTIOXIDANT CAPACITY AND PHENOL CONTENT IN FOUR CHEILANTHES SPECIES FROM NORTHERN WESTERN GHATS - Ghorpade, Pradnya Namdev (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The aim of current work was to assess the total phenolic content (TPC), total flavonoid content (TFC), phenolic compounds and antioxidant properties of different extracts of four Cheilanthes sp.: Cheilanthes farinosaÂ (Forssk.)Â Kaulf,Cheilanthes anceps Sw,Cheilanthes tenuifolia (Burm.f.) Sw, and Cheilanthes albomarginata Clarke which is collected from Northern Western Ghats of India. Methods: Analysis of the scavenging activity using 1, 1-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing power assays and N, N-dimethyl-p-phenylendiamine (DMPD) radical cation decolorization assay. Results: Cheilanthes sp. whole plant with rhizome was analyzed for total flavonoids content (TFC) and phenolic content (TPC). The ethyl alcohol and water are the best solvents for the extracting phenols and flavonoids from the Cheilanthes sp.whole plant with rhizome (CSWPR).The antioxidant activities of Cheilanthes sp.whole plant with rhizome extracts were a positive correlation between total flavonoids and phenolic content capacity and observed DPPH radical scavenging activity based on these results, the result signifies that the potentiality Cheilanthes sp.whole plant with rhizome is one of the natural sources of antioxidant compounds. Conclusion: We have reported in this study the cheilanthes species from whole plant with rhizome powder possess good antioxidant properties as well as their potential antioxidant capacity against DPPH radical, ferric reducing power and DMPD radical. Cheilanthes species whole plant with rhizome is a rich source of Phytochemicals including total antioxidant and phenolic compounds and it offers to the development of value-added products from Cheilanthes species whole plants so enhance today’s opportunities in nutraceuticals and food applications for Human Health.